The Socio-Economic Influence of Married Women Decision to Work as Family Walfare Improvement - Binti R; Lesta Karolina Br. Sebayang (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2017)
The purpose of this research is to draw industrial development strategy batik to increase the competitiveness of batik cluster Batangan in Batang distric. Methods used in research is quantitative descriptive using three of analysis is descriptive, policy analysis matrix (PAM) and analytic hierarchy process ( AHP ). The research results show obstacles in the development of cluster batik Batangan consisting of five major aspects that is aspects human resources, financial aspects, marketing aspects, raw materials aspects and technology aspects. Analysis pam obtained the result that cluster batik Batangan having competitiveness through the comparative excellences ( a value 0.25 ) or competitive advantage ( a value at 0.24 ). The results of analytic hierarchy process obtained development strategy cluster business batik Batangan consisting of five program criteria which are prioritized the first criteria raw materials ( a value weight 0,254), second financial criteria ( a value weight 0,231), third criteria technology ( a value weight 0,211), fourth criteria human resources ( a value weight 0,193) and fifth criteria marketing ( a value weight 0,111).